2016
DOI: 10.1016/j.hlc.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting Balloon Versus Second Generation Drug Eluting Stents in the Treatment of In-stent Restenosis: A Systematic Review and Meta-analysis

Abstract: While equipoise has been demonstrated in selected clinical outcomes between DEB and second generation DES in the treatment of ISR, the suboptimal angiographic outcome at follow-up and the higher TLR and MACE rates associated with DEB observed in the RCT are concerning. The results of the present analysis should be regarded as preliminary, although the generalised adoption of DEB in the treatment of ISR currently cannot be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
2
16
1
Order By: Relevance
“…With regards to MI and ST risk, similar to our overall effect estimates, none of the individual studies or previous meta‐analyses found a difference between the two treatment modalities . The definitions for MACE were heterogeneous among studies, thus we decided not to proceed with a meta‐analysis for this outcome.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…With regards to MI and ST risk, similar to our overall effect estimates, none of the individual studies or previous meta‐analyses found a difference between the two treatment modalities . The definitions for MACE were heterogeneous among studies, thus we decided not to proceed with a meta‐analysis for this outcome.…”
Section: Discussionsupporting
confidence: 68%
“…Last, one study that reported outcomes on patients treated with a sirolimus‐eluting newer generation stent, was excluded because the scope of this meta‐analysis was to compare DCB versus stents with the newer—limus substances (everolimus, zotarolimus, and biolimus). Ultimately, 10 studies were included in this systematic review and meta‐analysis . The PRISMA Flow Diagram presents the selection of studies in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of modality for a given case is very challenging because it is dictated by a large array of factors, in particular, stage of CAD (for example, stable CAD and acute myocardial infraction), demographic characteristics and health status of the patient (principally, age and comorbidities, such as diabetes mellitus and high risk for bleeding), location of the lesion in the artery (for example, on a curve or immediately followed by a curve or at the left main stem); type of lesion (such as plain single-vessel, bifurcation single-vessel, plain multi-vessel, and calcified lesions); size of the artery (for example, < or >3 mm); degree of occlusion/blockage of the artery (that is, ratio of lesion size to artery size); and presence or absence of ancillary cardiovascular conditions (for example, myocardial infarction, saphenous vein graft disease and diffuse disease requiring 4 ormore stents) [25] [26] [27]. This challenge is manifest in the fact that, in spite of a voluminous body of literature comprising randomized controlled trials (RCTs), systematic review of results of RCTs, and meta-analyses of the results of RCTs in which the subject is either one modality or two or more [21] [28] [29] [30], there is a lack/shortage of evidencebased recommendations. This has led to guidelines; for example, in 2014, the European Society of Cardiology listedpolymer-coated drug-eluting stents and BCA as preferred procedures [30] and European and US guidelines call for the use of a "Heart Team" (comprising clinical cardiologists(s), interventional cardiologist(s), and cardiothoracic surgeon(s)) in making a decision on modality to use for a particular case [15].…”
Section: Introductionmentioning
confidence: 99%